The Use of English as a Medium of Instruction: Issues and Challenges in a Private Technological University - Chong, Su Li (2008)
Malaysia is made up of an array of ethnic groups and cultures. As such, most Malaysians are multilingual. Several languages are used in this country wherein Bahasa Malaysia (Malay) is the national language. The education system in Malaysia also predominantly uses Malay as its medium of instruction. However, there are also bilingual education systems that use mother tongue languages such as Mandarin or Tamil with Malay. Higher learning institutions in Malaysia also predominantly use the Malay language. On the other hand, the status of English in Malaysia is as a second language. In this paper, we aim to explore the issues and challenges related to the use of English as the medium of instruction in a private technical university in Malaysia. This technical university has taken a bold stand to use English instead of the Malay language. This is done so that the university can be recognized as an international university. Moreover, the university’s population is also made up of international students and staff. However, in doing so, the community of the university contend with various issues and challenges when communicating in English, both within and outside the classrooms. The researchers explored these issues and challenges from the perspectives of the academics and administrators of the university. Specifically, the researchers examined the language policy of the university and to what extent the policy is supported by conditions and contexts within the university. Findings from this study will enable the academics and administrators to better understand the complexities that come from the challenges and issues in adopting English language as a medium of instruction in this university.